Iron Oxide Nanoparticle Uptake in Mouse Brachiocephalic Artery Atherosclerotic Plaque Quantified by T(2)-Mapping MRI - Moonen, Rik P. M. (Pharmaceutics, 2021)
The purpose of our study was to monitor the iron oxide contrast agent uptake in mouse brachiocephalic artery (BCA) atherosclerotic plaques in vivo by quantitative T(2)-mapping magnetic resonance imaging (MRI). Female ApoE(−/−) mice (n = 32) on a 15-week Western-type diet developed advanced plaques in the BCA and were injected with ultra-small superparamagnetic iron oxides (USPIOs). Quantitative in vivo MRI at 9.4 T was performed with a Malcolm-Levitt (MLEV) prepared T(2)-mapping sequence to monitor the nanoparticle uptake in the atherosclerotic plaque. Ex vivo histology and particle electron paramagnetic resonance (pEPR) were used for validation. Longitudinal high-resolution in vivo T(2)-value maps were acquired with consistent quality. Average T(2) values in the plaque decreased from a baseline value of 34.5 ± 0.6 ms to 24.0 ± 0.4 ms one day after injection and partially recovered to an average T(2) of 27 ± 0.5 ms after two days. T(2) values were inversely related to iron levels in the plaque as determined by ex vivo particle electron paramagnetic resonance (pEPR). We concluded that MRI T(2) mapping facilitates a robust quantitative readout for USPIO uptake in atherosclerotic plaques in arteries near the mouse heart.